Pengaruh Kebijakan Moneter dan Fiskal terhadap Pembangunan Ekonomi - Nuzul Fikri Ramdani; Rozzy Apprirachman (Jurnal Bersama Ilmu Ekonomi (EKONOM), 2025)
Economic development is a multidimensional process that not only reflects an increase in per capita income but also entails structural transformations in social, institutional, and behavioral aspects of society. In the context of Indonesia, monetary and fiscal policies are two essential macroeconomic instruments that shape the direction and success of economic development. This study aims to analyze the contribution and effectiveness of both policies in fostering inclusive and sustainable economic growth. Employing a qualitative approach through literature review, this research examines academic publications, official reports, and secondary data sources. The findings indicate that monetary policy through interest rate management, money supply control, and exchange rate stabilization plays a critical role in maintaining price stability and supporting economic activity. Meanwhile, fiscal policy via government spending, subsidies, taxation, and public debt instruments contributes to reducing social inequality and enhancing public welfare. The synergy between these two policy domains is pivotal in achieving macroeconomic stability and promoting equitable national economic development. Therefore, the formulation and implementation of integrated, adaptive, and context-sensitive economic policies are crucial to respond effectively to both domestic and global economic dynamics.